A study of influences of the workers’ compensation and injury management regulations on aviation safety at a workplace - Yadav, D.; Nikraz, Hamid; Chen, Y. (Taylor & Francis, 2016)
As the aviation industries developed, so too did the recognition that there must be an effective regulatory framework to address issues related to the workers’ compensation and rehabilitation. All employees would like to work and return home safely from their workplace. Therefore, the efficient management of workplace injury and disease reduces the cost of aviation operations and improves flight safety. Workers’ compensation and injury management laws regulate a majority of rehabilitation and compensation issues, but achieving an injury-free workplace remains a major challenge for the regulators. This paper examines the clauses of the workers’ compensation and injury management laws of Western Australia related to workplace safety, compensation, and rehabilitations of the injured workers. It also discusses various provisions of common law under the relevant workers’ health injury management legislations.